Efek Pemberian Kulit Buah Naga merah (Hylocereus polyrhizus) terhadap Tebal Endometrium dan Miometrium Tikus Model Menopause - Wong, Ferdinand; Sugiritama, I Wayan; Ratnayanti, I Gusti Ayu Dewi; Wahyuniari, Ida Ayu Ika; Wiryawan, I Gusti Nyoman Sri (Universitas Udayana, 2023)
ABSTRACT Effects of Giving Red Dragon Fruit Skin (Hylocereus polyrhizus) as Phytoestrogens on Endometriak Thickness and Myometrium of Menopausal Model Rats Background: Menopause is a condition in which the body experiences a lack of estrogen due to decreased ovarian function. Decreased estrogen levels result in particular changes in the thickness and shape of the uterus. Phytoestrogens are herbal compounds that have several similarities to the functions and structures of estrogen. Phytoestrogens also can be an alternative as a therapeutic option when they need a substitute for estrogen. Among several types of phytoestrogens, anthocyanin is one of the potential. Anthocyanins are mostly found in the red dragon fruit, Hylocereus polyrhizus. Red dragon fruit skin contains anthocyanins. Anthocyanins compounds have the potential to overcome the symptoms caused by menopause through their phytoestrogens and antioxidant activity.Objective: The main purpose of this study is to determine the effect of red dragon fruit skin extract (Hylocereus polyrhizus) on the thickness of the endometrium ad myometrium in menopausal model rats. Methods: This study applied a randomized post-test only control group design using a sample of 30 female wistar rats that met the inclusion and exclusion criteria. The sample was divided into 3 (three) treatment groups where a group was consisted of 10 female wistar rats. The treatment group 1 was the control group, while the treatment group 2 was the group given the ethanol extract of red dragon fruit skin at a dose of 60 mg/200 grBW/day for 30 days, and the treatment group 3 was the group given the ethanol extract of red dragon fruit skin at a dose of 90 mg/200 grBW/day for 30 days. Results: The study signified an increase in the endometrial thickness after being given red dragon fruit extract (Hylocereus polyrhizus) at a dose of 60 mg/200 grBW and 90 mg/200 grBW in menopausal model rats. In the single-lane ANOVA test, the thickness of the endometrium found a significance value of 0.038 (p<0.05), while the thickness of the myometrium found a significance value of 0.000 (p<0.05).